Paint shop scheduling in a bus plant :|re-entrant hybrid flow shop model with zero buffer and no-wait stations - Veysel, Ebru. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
In this study, an optimization model is constructed to propose the scheduling plan for a paint shop of a bus production plant. In bus production plant, the paint shop is located between the body shop and assembly line. Both the release time and the delivery time of the buses are restricted and in takt time base. Although the buses follow single flow line in body shop and assembly line, due to painting variety options, buses re-visit some of the operations more than once depending on the color and decorations of the buses. There are identical parallel machines operate the same processes. The paint shop has limited space for buffers since the buses are large items and production area is valuable due to operating costs. Some stations can be used as buffer if the next station is blocked by another job. On the other hand, due to the nature of the operations some stations cannot be used after the process is finished, those are called no-wait stations. There are many studies in literature that cover some of the issues mentioned above. However, no study is found that covers all those in their scope. We propose a linear mixed integer programming model that covers re-entrance, zero buffer, and no-wait stations in hybrid flow shop. The objective is to minimize the total tardiness with a stepwise cost function. The model is tested with combination of two different real case parameters, which are the changing re-entrant job ratios and the increasing daily production volume.
Keywords: Production scheduling.; Dyes and dyeing.